Tribological Evaluation of Canarium Shweinfurthi (African Elimi) Oil as Lubricant in Metal Forming - Kamtu, P. M.; Gukop, N. S.; Ashwe, A.; Gundu, D. T.; Albert, W. Y. T.; Babawuya, A.; Popoolao, C. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
Reducing cost of production arising from high energy due to friction and tool failure using cheaper readily available and environment friendly lubricant is evaluated in this study. An experimental evaluation of tribological properties of Canarium Shweinfurthi (African Elimi) was carried out using Ring Compression Test. This was carried out using Boron Nitride as additive to determine the best quantity that can be added in vegetable oil lubricants. The formulated oils were applied to the die/ring surfaces as they were compressed in the Califonia Bearing Ratio (CBR) using digital display Testometric Universal Testing Machine. The results show that friction factors for the developed lubricant range between m = 0.3 and 0.4 while the frictional coefficient results show μ = 0.07 to 0.09 which compared favorably to referenced (mineral) oil which has m = 0.4 and μ = 0.12. Additionally, frictional coefficient obtained from the developed lubricant are within the range for vegetable lubricants such as groundnut oil, palm oil, palm kernel and shear oil which range from 0.072 to 0.3. Furthermore, it was observed that Canarium Shweinfurthi oil could be used as substitute to mineral based oils that are currently in use as lubricants in manufacturing process. Therefore, industrial organizations can take advantage of the benefits this natural, environmentally friendly, biodegradable and low toxicity oil lubricant presents.